Aerobic denitrification using Bacillus pumilus, Arthrobacter sp., and Streptomyces lusitanus: Novel aerobic denitrifying bacteria. (June 2021) - Elkarrach, Karima; Merzouki, Mohammed; Atia, Fatima; Laidi, Omar; Benlemlih, Mohamed
Abstract: Aerobic denitrification capacity of some strains is not yet shown. Consequently, this study aimed to isolate new aerobic denitrifying strains, to identify them, and finally to test their aerobic denitrifying potential. Three strains were isolated and they have shown a high aerobic denitrification capacity. These strains were identified as Bacillus pumilus, Arthrobacter sp., and Streptomyces lusitanus . After 48 h, the nitrate removal achieved 99.7%, 98.98%, and 99.81% respectively for Bacillus pumilus, Arthrobacter sp., Streptomyces lusitanus, and their consortium. These removals were occurred using a bacterial concentration of 6%, an initial nitrate concentration of 70 mg/L, sodium acetate as carbon source, a temperature of 37 °C, and shaking at 150 rpm. In conclusion, these isolated strains can be considered as a future solution for removing nitrate from contaminant resources, or they can be added to various biological processes to eliminate nitrate from the wastewater. Graphical abstract: Unlabelled Image Highlights: Bacillus pumilus, Arthrobacter sp., and Streptomyces lusitanus were isolated. The three isolates have shown a good aerobic denitrification capacity. A simultaneous nitrate and COD removals have shown for the three isolates. Bacillus pumilus and consortium gave a high nitrate and COD removals. Bacterial concentration 6% had a significant effect on nitrate and COD removals.